2019
DOI: 10.1002/jmv.25540
|View full text |Cite
|
Sign up to set email alerts
|

Validity of administrative database detection of previously resolved hepatitis B virus in Japan

Abstract: The risk of hepatitis B virus (HBV) reactivation has increased owing to advances in the immunosuppressive therapy field. However, the HBV reactivation incidence among patients with previously resolved HBV (prHBV) infection during immunosuppressive therapy for rheumatoid arthritis (RA) remains unclear. The objective of this work is to describe the validity of detecting prHBV infection from administrative data through comparisons with chart abstraction and determine the incidence of HBV reactivation during immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…The NCDA is based on the Standardized Structured Medical Record Information Exchange (SS-MIX), including medical charts, laboratory data, bacterial culture data, and many other data fields on daily basis [ 14 , 15 ]. Additional details have been reported elsewhere [ 12 , 13 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“… 20 Imai et al described the validity of detecting previously resolved hepatitis B virus infection in the NHO database with the chart review as the golden standard, with the positive predictive value (PPV) of 85.8%. 21 In addition, the validation study of comparison with the procedure-based and the diagnosis-based identifications of severe sepsis and disseminated intravascular coagulation in administrative data was conducted. 22 This validation study showed that the procedure-based algorithm is more sensitive than the diagnosis-based algorithm and has the potential to improve the likelihood of disease identification from the NHO database.…”
Section: Data Resource Usementioning
confidence: 99%